CHEMICAL CONTROL OF ASIAN SOYBEAN RUST IN SOUTH PARANÁ STATE - REIS, Emerson Fábio dos; LIMA NETO, Vismar da Costa; GODOY, Cláudia Vieira; ROSA, Cleber Teixeira; CASTANHO, Hailton Ezequiel; VICENTE, Nilson Gonçalves (Scientia Agraria, 2007)
Asian soybean rust, caused by the fungus Phakopsora pachyrhizi, is a recent problem on soybean in Brazil. Affected plants shed their leaves prematurely leading to crop losses. The present work was undertaken with the aim of testing two fungicidal active ingredients and 5 application times. The trials were established in Palmeira, from November 2003 to May 2004, with the cultivars CD 205 and BRS133. The active ingredients (a.i) assayed were tetraconazol (50g a.i. ha-1), and pyraclostrobina (66.5g a.i. ha-1) + epoxiconazol (25g a.i. ha-1). One application at stages V7 (initial disease symptoms), V9, R1, R2 and R5.1 was compared with one and two applications at stages R2 and R5.1. Trials were carried out using randomized block designs with four replicates and variable numbers of treatments per trial (nine treatments on the cv. BRS 133 and seven on the cv. CD 205). The harvest area of each plot was 5,4 m2. The treatments with triazol and the mixture of estrobirulina + triazol showed protective and curative efficiency on Asian soybean rust with similar disease control. The treatment with tetraconazol and pyraclostrobina + epoxiconazol showed higher efficiency when applied under low fungal severity. However, it was verified that the first application of fungicide at stage V7 on cv. BRS 133 and R1 on cv. CD 205 resulted in a slower evolution of the rust severity.